Automated lab attendance system (ALAS) - Noorbaiti, Mahusin (2005)
People use attendance system to record activities. Attendance is being used in business agencies, industries, universities and etc.Attendance system will be very much of help in monitoring their employee attendance, absence and leave application.In Universities, the attendance system can be used by the lecturers on taking students attendance for their class.Furthermore, the system can assist in the management of lab security by recording students entring the lab.Currently, most universities record the student attendance manually.This has creates problems such as data loss,unreliable information and etc.The security of laboratory can also be strengthened by having information of students entering laboratories.The main purpose of this system is to help the lecturers in taking the students attendant,as well as to control the laboratory door access. A prototype of the Automated Lab Attendance System (ALAS) system is developed to assist lecturers to manage class atteridnce,and to asist Laboratory Administrator in keeping track of the laboratory users.